2014
DOI: 10.3109/0284186x.2014.918276
|View full text |Cite
|
Sign up to set email alerts
|

Efflux pump ABCB1 single nucleotide polymorphisms and dose reductions in patients with metastatic renal cell carcinoma treated with sunitinib

Abstract: (2014) Efflux pump ABCB1 single nucleotide polymorphisms and dose reductions in patients with metastatic renal cell carcinoma treated with sunitinib,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 20 publications
1
25
0
Order By: Relevance
“…On PK, the results show that SNPs in genes coding for CYP enzymes, CYP regulators, and drug efflux transporters (ABCB1, ABCC2, and ABCG2) seem to play an important role in sunitinib treatment outcome, especially CYP3A5 and ABCB1 SNPs [19][20][21]29,31,34,37]. In some of the articles on sunitinib, the intermediate endpoints clearance and exposure were investigated and confirmed the hypotheses that SNPs in CYP3A4, CYP3A5, and ABCB1 influence drug exposure [22,29,36,37] (Figure 2).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…On PK, the results show that SNPs in genes coding for CYP enzymes, CYP regulators, and drug efflux transporters (ABCB1, ABCC2, and ABCG2) seem to play an important role in sunitinib treatment outcome, especially CYP3A5 and ABCB1 SNPs [19][20][21]29,31,34,37]. In some of the articles on sunitinib, the intermediate endpoints clearance and exposure were investigated and confirmed the hypotheses that SNPs in CYP3A4, CYP3A5, and ABCB1 influence drug exposure [22,29,36,37] (Figure 2).…”
Section: Discussionmentioning
confidence: 86%
“…In a study of Beuselinck et al, an increased time-to-dose reduction was seen for the TT genotype patients of rs1128503 and rs2032582 in ABCB1 compared to C-allele and G-allele carriers, respectively [21].…”
Section: Pharmacogenetics To Predict Sunitinib Toxicitymentioning
confidence: 99%
“…In 19 Japanese patients with renal carcinoma, the C1236T, G2677T/A and C3435T polymorphisms had no effect on kinetics [136]. One study of 88 mainly Caucasian renal cancer patients showed an association of the 1236TT genotype with lower overall and progression-free survival rates [137], and a subsequent analysis reported less need for dose reductions due to adverse effects [138]. However, a multicentre, observational, prospective study including 101 patients with advanced renal cell carcinoma treated with first-line sunitinib did not show any significant influence of the ABCB1 genotype [139].…”
Section: Sunitinibmentioning
confidence: 94%
“…Herein, we have focused on SNPs that were very likely to have an effect on VEGF or VEGFRs, or SNPs that have a high biomarker potential because of confirmatory findings in large cohorts. Thirteen SNPs were selected located in CYP3A5, ABCB1, VEGF-A, VEGFR-2, VEGFR-3, and interleukin-8 [9][10][11][12][13][14][15][16][17][18][19][20][21][22] (details are provided in Supplementary Material S1).…”
Section: Snp Selection and Genotypingmentioning
confidence: 99%
“…8 With regard to genetic predictors, previous studies associated single nucleotide polymorphisms (SNPs) in genes encoding metabolizing enzymes or transporters related to pharmacokinetics (PKs) and pharmacodynamics (PDs) of sunitinib with efficacy and toxicity. [9][10][11][12][13][14][15][16][17][18][19][20][21][22] In order to find predictive biomarkers for the clinical outcome of sunitinib, a better understanding of the relationships between sunitinib exposure, the pharmacological response, and the clinical outcomes is vital. This is part of the objectives of the European collaborative project Euro-TARGET.…”
mentioning
confidence: 99%